Improved Malaria Therapy with Cationic Nanocapsules Demonstrated in Plasmodium berghei-Infected Rodents Using Whole Blood Surrogate Population PK/PD Modeling - Tamara Ramos Maciel; Ana Claudia Funguetto-Ribeiro; Laura Ben Olivo; Flávia Elizabete Guerra Teixeira; Camila de Oliveira Pacheco; Bibiana Verlindo de Araujo; Sandra Elisa Haas (MDPI AG, 2024)
Objectives: Investigating how nanoparticle systems interact in whole blood (WB) is critical to evaluating the effectiveness of malaria therapy. Methods: We decided to establish a pharmacokinetic/pharmacodynamic (PK/PD) model of the quinine population in WB using Plasmodium berghei-infected mice, with a subsequent model comparison for nanocapsules coated with polysorbate (NCP80) or prepared with Eudragit® RS (NCEUD). The WB quinine population pharmacokinetic model in rats was developed using plasma and partition coefficients for rat erythrocytes. Mouse WB quinine population PK/PD modeling was developed using allometrically scaled literature-free mouse quinine pharmacokinetic data and covariate values to obtain a WB population pharmacokinetic model for quinine and nanocapsules in mice. This allowed for PK/PD modeling of the quinine population with the WB concentration and parasitemia data in mice. All models were built in NONMEN. Results: The WB quinine concentration profiles in rats were characterized using a two-compartment model. Nanoencapsulation reduced clearance and central compartment volume and increased peripherical compartimental volume. A maximum effect model described the PK/PD of the quinine WB population in mice, demonstrating that NCEUD enhances the antimalarial effect. Conclusions: Quinine WB is a good surrogate for describing the response to exposure in malaria. NCEUD outperformed NCP80 and free quinine, suggesting that cationic surfaces improve the potential for treating malaria.